A Phase II Study of Concurrent Chemoradiotherapy With Paclitaxel and Cisplatin for Inoperable Esophageal Squamous Cell Carcinoma. (August 2016) - Tang, Hua-Rong; Ma, Hai-Feng; An, Shi-Min; Badakhshi, Harun; Deng, Jia-Ying; Zhang, Jun-Hua; Chen, Yun; Zhang, Zhen; Guo, Xiao-Mao; Jiang, Guo-Liang; Zhao, Kuai-Le
Abstract : Objectives: A phase II study was performed to investigate the efficacy and the safety of a 3-week schedule of paclitaxel (PTX) plus cisplatin (DDP) combined with concurrent radiotherapy for esophageal squamous cell cancer. Patients and Methods: Patients with newly diagnosed esophageal squamous cell cancer who had histologic proof of local-regional carcinoma of the esophagus, a Karnofsky performance status of 80 or greater, and normal liver, renal, and bone marrow functions were enrolled in the phase II trial. Chemotherapy consisted of DDP (25 mg/m 2 /d) for 3 days plus PTX (175 mg/m 2 ) given for 3 hours, every 3 weeks for 4 cycles. The total dose of concurrent radiation with 68.4 Gy/44 Fx (late course–accelerated radiotherapy) or 61.2 Gy/34 Fx (conventional radiotherapy) was given at the first day of chemotherapy. Results: Between July 2008 and November 2011, 76 patients were enrolled in this trial. The median age was 58 years (range, 37 to 74 y). The stages were stage II (21 patients), stage III (27 patients), and stage IV (28 patients). A total of 89.5% (68/76) and 63.2% (48/76) patients completed ≥2 cycles and all 4 cycles of chemotherapy, respectively. With the median follow-up of 36 months, the overall median survival time was 28.5 months and the progression-free survival time was 14.7 months. One- and 3-year survival rates were 75% and 41%, respectively. Neutropenia grade 3 and 4 occurred in 30.3% and 31.6% of the patients, respectively. Conclusions: Radiotherapy concurrent with a 3-week schedule of PTX and DDP resulted in an encouraging overall survival rate, but a relatively higher hematological toxicity.